Higher education and sustainability of beef cattle in the village of South Sulawesi Indonesia - Haeruddin Saleh,; Muhammad Idris,; Sri Firmiaty, (Technium Social Sciences Journal, 2020)
Bone Regency is an agricultural area that includes food crops, livestock, and fisheries. This area is a very large producer of livestock, so this study analyzed how the influence of tertiary institutions in their role in the form of community service in the form of assistance to groups of farmers in the area, especially in the village of Bune. In this study using the method used quantitatively to see the role of tertiary institutions, data were obtained through a questionnaire with a sample of 30 people and the statistical tools used were Path Analysis is to compare all the variables used so that there is a picture of the role of tertiary institutions in the development of farmers' businesses in the village of Bune. The results of the research show that with the assistance provided by tertiary institutions, it can improve the competence of cattle ranching, namely technically, entrepreneurial and managerial abilities, from these variables after being analyzed using statistics shows that technical competence, entrepreneurship, and managerial influence the increase in productivity, so that the cattle farming business managed by the community in Bune Village can be sustainable.